2016
DOI: 10.1007/s10902-016-9761-x
|View full text |Cite
|
Sign up to set email alerts
|

A Positive Perspective on Attentional Bias: Positive Affectivity and Attentional Bias to Positive Information

Abstract: In recent years there has been growing interest in determining the attentional basis of positive affectivity. Investigators have sought to evaluate the hypothesis that elevated positive affectivity is characterized by an attentional bias that favours the processing of positive information over neutral information. Unfortunately, in the studies carried out to date, the assessment procedures used by researchers to assess such attentional selectivity have either been methodologically limited or methodologically f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
1
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 46 publications
1
11
1
4
Order By: Relevance
“…They found that people who tended to experience higher levels of positive affect, as assessed 5 times per day for a 1 week period, demonstrated disproportionately speeded responses to probes appearing in the locus of positive words, relative to those that appeared in the locus of neutral words, indicating an attentional bias towards the positive information. These findings have recently been replicated by Grafton and MacLeod (2016), who recruited participants reporting either high or low levels of positive affectivity, and had them perform a similar attentional probe task. The participants high in positive affectivity displayed greater speeding to process probes in vicinity of the positive information, compared to probes in the vicinity of the neutral information, further supporting the hypothesis that elevated positive emotional disposition is characterized by an attentional bias to affectively positive information.…”
Section: Does Attentional Bias To Affectively Positive Information Contribute To Positive Emotional Disposition?mentioning
confidence: 71%
“…They found that people who tended to experience higher levels of positive affect, as assessed 5 times per day for a 1 week period, demonstrated disproportionately speeded responses to probes appearing in the locus of positive words, relative to those that appeared in the locus of neutral words, indicating an attentional bias towards the positive information. These findings have recently been replicated by Grafton and MacLeod (2016), who recruited participants reporting either high or low levels of positive affectivity, and had them perform a similar attentional probe task. The participants high in positive affectivity displayed greater speeding to process probes in vicinity of the positive information, compared to probes in the vicinity of the neutral information, further supporting the hypothesis that elevated positive emotional disposition is characterized by an attentional bias to affectively positive information.…”
Section: Does Attentional Bias To Affectively Positive Information Contribute To Positive Emotional Disposition?mentioning
confidence: 71%
“…face validity). Indeed, although high TPA individuals favor processing positive vs. negative information, positive features of hiring procedures must exist to be perceived and instantiate favorable behavioral intentions (Grafton and MacLeod, 2017). On the other hand, our work seems to suggest that, to some degree, applicant reactions are outside of an organization's control.…”
Section: Discussionmentioning
confidence: 99%
“…Crossfield dan Damian menambahkan bahwa informasi yang bersifat emosional (bervalensi) dapat memengaruhi pemrosesan informasi. Hal ini didukung oleh penelitian yang menunjukkan bahwa informasi emosional dapat menimbulkan bias atensi emosional (Grafton & MacLeod, 2017;Karademas et al, 2007;Segerstrom, 2001).…”
Section: Pendahuluanunclassified
“…Secara spesifik peneliti meyakini bahwa afek positif dapat memengaruhi pemorsesan informasi pada remaja. Afek positif terbukti dapat menimbulkan waktu reaksi yang lebih lama untuk memproses informasi bervalensi positif atau mengindikasikan adanya gangguan pada inhibitory control (Grafton & MacLeod, 2017) Terutama jika afek positif ini berkaitan dengan approach motivation yaitu motivasi yang menyebabkan individu terdorong untuk menghadapi atau mendekati suatu objek. Oleh karena itu, peneliti menduga bahwa terdapat peran mediasi dari kondisi afek positif di dalam hubungan antara efikasi diri dan bias atensi emosional pada remaja.…”
Section: Pendahuluanunclassified